Race : the history of an idea in America - Gossett, Thomas F., 1916-2005 (Race and American culture., 1997)
When Tom Gosset's Race: The History of an Idea in America appeared more than a generation ago, it explored the impact of race theory on literature in a way that anticipated the entire current scholarly discourse on the subject. Though it has gone out of print, it has never been rendered obsolete. Its reprinting is a boon to younger scholars in particular who are unfamiliar with its rich presentation of fact and its clear, efficient analysis, from which so much later theorizing has developed. With a new afterword by and about the author, and an introduction by series editors Arnold Rampersad an.